A REDE EDUCACIONAL JAPONESA DA BAIXADA SANTISTA E VALE DO RIBEIRA (1908 – 1945) - SILVA, Rafaela da Silva e (2016)
The present text, outcome of a thesis for the Doctorate in Education course, of the Post-Graduation Program from “Universidade Metodista de São Paulo”, with the objective of analyzing the Japanese educational network as well as its performance in “Baixada Santista” and “Vale do Ribeira” regions, by the seaside and southern region of São Paulo State respectively in the first half of the twentieth century (1908-1945). The bibliography which explores the subject about the Japanese immigration is very cohesively regarding Education. It was really common, among several Japanese colonies that rose in São Paulo State and other places from Brazil, the presence of schools available for the Japanese language teaching, moreover, the school represented a symbol of progress and prosperity for the colony. The same happened in the regions studied by the present research, where we could find many schools built with the own Japanese settlers’ efforts. From the decade of 1920 on, the Japanese government started supporting directly the Japanese-Brazilian Education by the Japanese Consulate, creating for that the Difusion Society of Japanese Teaching in Brazil. This way, is it possible to question to what extent the actions of the Japanese government interfered in the operation of these schools and, in fact, established a centralizer character to them? Were there nationalist interests behind the centralization try? Did this institution interfere in the performance of schools made by Japanese immigrants? Which was its impact in the educational daily of Japanese colonies at their respective schools? What was in fact its function as institution linked to Japanese education in Brazil? In order to answer such questions, the research counted on some more in-depth references about the Japanese immigration and its education as form of understanding of the phenomena, with the objective is to give theorical support to primary historical sources found, for instance, Arlinda Rocha Nogueira, Zeila de Brito Fabri Demartini, Hiroshi Saito, among others. Supported by the bibliography, the research looked for printed documentary sources, such as photos, school books, books produced at that time by the colony, etc., and research of Oral History achieved since 2008 with former students of Japanese schools as well as people who had some close relation with the Japanese colonies. The study observed the Difusion Society of Japanese Teaching in Brazil was crucial to give centrality to the Japanese language teaching, making easier the send and qualification of teachers, dispatching material, besides providing didactic financial support to schools. On the other hand, the institution was right target of the nationalist actions of Getúlio Vargas’ totalitarian state during the New State (1937), being obliged to cease its activities at the Japanese schools . The Difusion Society of Japanese Teaching in Brazil was primal to guarantee the Japanese language teaching as long as possible at Vargas’ Period and the repression to immigrant education.